2013
DOI: 10.1371/journal.pone.0073436
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of E2F1 Promotes Tumor Malignancy And Correlates with TNM Stages in Clear Cell Renal Cell Carcinoma

Abstract: BackgroundTranscription factor E2F1 exerts effects on many types of cancers. As an upstream regulator of a host of genes, E2F1 can trigger diverse aberrant transcription processes that may dominate malignancy. Clear cell renal cell carcinoma (ccRCC) is the most common subtype in renal cell carcinoma which displays high malignancy and has a shortage of biomarkers in clinics. Our study aimed to explore the function of E2F1 in ccRCC and its correlation with clinicopathological parameters.Methodology/Principle Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 26 publications
5
50
0
Order By: Relevance
“…In adult clear cell renal cell carcinoma (ccRCC), E2F1 has been shown to be elevated in several studies 23, 24 , which is consistent with the results presented here. This is likely due, at least in part, to the observation that the protein product of the VHL gene (pVHL) inhibits E2F1 expression 23 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In adult clear cell renal cell carcinoma (ccRCC), E2F1 has been shown to be elevated in several studies 23, 24 , which is consistent with the results presented here. This is likely due, at least in part, to the observation that the protein product of the VHL gene (pVHL) inhibits E2F1 expression 23 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, E2F’s have been shown to be elevated in adult renal malignancies 23, 24 . We therefore interrogated other members of the E2F gene family and found E2F1 is part of the concordant gene signature shared by human WT’s and murine Kras G12D /Catnb Δex3 tumor bearing kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…Certain studies reported that E2F1 disrupts a range of pathways in numerous cancers and is closely correlated with clinical parameters (13)(14)(15). We had also previously identified that E2F1 is upregulated in ccRCC progression (16).…”
Section: Introductionmentioning
confidence: 70%
“…Few pathways were attenuated after RB depletion, despite the total number of genes altered in this category, underscoring the focused nature of E2F1 activity to elicit specific transcriptional programs. Pathways with attenuated enrichment include those that have been previously shown to interplay with the RB/E2F1 axis, such as epithelial-mesenchymal transition, hedgehog signaling, and myogenesis (Figure 6C, left; normalized enrichment score < -1.3) (59)(60)(61)(62)(63)(64). Conversely, a number of clinically relevant pathways were enriched upon RB loss, including canonical E2F targets, Myc targets, mitotic spindle, and DNA repair (Figure 6C, right; normalized enrichment score > 1.3).…”
Section: Delineation Of the Rb Loss-induced Transcriptomementioning
confidence: 99%